THE CORRELATION BETWEEN THE QUALITY OF WORK LIFE AGAINST THE PERFORMANCE OF THE EMPLOYEES OF OGAN ILIR DISTRICT GENERAL HOSIPTAL, SOUTH SUMATERA IN 2018 - Yadi, Herliyanti; Ayuningtyas, Dumilah (Journal of Indonesian Health Policy and Administration, 2020)
A favorable work environment will influence the quality of work life, would create quality human resources, and support the improvements in the quality of services. To discover the correlation betweem the quality of work life and the employees’ performance at Ogan Ilir District General Hospital, a study was performed in March-April 2018. The study was a cross sectional quantitative study on 315 civil servants and voluntary staff at the hospital. Univariate, bivariate, and multivariate analysis was performed using the chi-square and the double regression prediction/determinant model. We discovered that the quality of the work life at the hospital was lacking, particularly for pride in their place of work, employee involvement/participation, and the facilities provided to the employees. It was also discovered that of the 315 employees, 164 (51.1%) employees had low performance index and there was a significant correlation between the employee involvement/participation and the facilities provided to the employees with their performance. Therefore, the three components that was correlated strongly with employee performance was employee involvement/participation [Odds Ratio (OR): 2.190, Confidence Interval (CI): 95%, P <0.001], facilities provided (OR: 2.670; CI 95%, p < 0.000), and work safety (OR: 0.972, CI 95%, p = 0.911).